PENGARUH PENGELASAN GTAW PADA LOGAM BIMETAL PLAT BAJA KARBON RENDAH DAN STAINLESS STEEL TERHADAP SIFAT MEKANIK SAMBUNGAN LAS - Lisa Agustriyana; Sarjiyana Sarjiyana; Suyanta Suyanta (Universitas Lambung Mangkurat, 2019)
Stainless steel material (stainless steel) is used in the home industry and the military industry, and also in the nuclear industry. Steel material is divided into five types, namely austenite, ferrite, martensite, duplex and precipitation hardening. Ferritic stainless steel is an attractive alternative in vehicle production because of its corrosion resistance. Different metals have different characteristics from one another, so the welding process of dissimilar metals requires certain techniques. The purpose of this study is to determine the tensile strength of welds in bimetallic welding between low carbon steel plates and stainless-steel plates and to know the hardness of welds in bimetal welding between low carbon steel plates and stainless-steel plates using GTAW welding. The research method used: this research is part of the testing of technical materials conducted by the destructive test method with the category of science and technology development in the field of Mechanical Engineering. There is a trend of increasing tensile strength, yield strength and hardness of bimetallic welding of low carbon steel plates and stainless-steel plates using GTAW welding, that the greater the welding amperes will increase tensile strength, yield strength and hardness. The highest tensile strength was 41.18 Kg / mm2 and the highest yield strength was 41.16 Kgf / mm2 at 60 amperes and the highest hardness was 571.01 BHN at 55 amperes with the corresponding amperage range from the usage table 45 - 65 amperes. In the HAZ area when compared to the parent material, the HAZ area hardness is higher than the parent material and lower than the weld filler.